Respuesta :
Answer:
(7 -7)
Step-by-step explanation:
Y= -4x +5-----------1
Y= 3x -16----------2
Y-5= 4x
X= (y-5)/4
Substitute in (eqn 2)
( tired )
The solution to the system of equations y = -4x + 5 and y = 3x - 16 is x = 3 and y = -7
Given the system of equations:
y = -4x + 5 (1)
y = 3x - 16 (2)
Substitute y = -4x + 5 in equation 2:
-4x + 5 = 3x - 16
7x = 21
x = 3
Put x = 3 in y = -4x + 5:
y = -4(3) + 5
y = -7
The solution to the system of equations y = -4x + 5 and y = 3x - 16 is x = 3 and y = -7
Find out more at: https://brainly.com/question/9585437